WebGIS development for base flow separation and recharge estimation - Bortolin, Taison Anderson; dos Santos, Lucas Moraes; da Silva, Adriano Gomes; Schneider, Vania Elisabete (Revista de Informática Teórica e Aplicada, 2020)
The basic flow rate is characterized by an important hydrological component being responsible for the estimation of the water recharge. Due to the difficulty of measurement, mathematical methods are used to calculate the flow separation. However, when hydrographic analysis is based on long historical series, the use of these methods becomes impracticable, making it necessary to use computational resources. A WebGIS (Web Geographical Information System) was developed for data selection and calculation of base flow separation, based on hydrological data from fluviometric stations located in the Taquari-Antas basin, located in the state of Rio Grande do Sul. A modified version of the Unified Process was used as a software development methodology. We used the MVC software architecture standard and the programming languages PHP 7.0, HTML5, JS and CSS3 for programmatic development of the constituent layers of the system. The hydrological data comes from the HIDROWEB portal, part of the National Information System on Water Resources (SNIRH), with hydrological information collected by the National Hydrometeorological Network (RHN) coordinated by the National Water Agency (ANA). The system facilitates the use of remote and distributed hydrological data, shared over the Internet, for various hydrological analyzes.